John Locke on Just Price: A Commentary on "Venditio" - Mack, Eric (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2024)
Locke’s short essay, “Venditio,” offers a series of thought-provoking examples of prices that might or might not be viewed as just. Locke writes as though these examples and his comments about them point to a coherent doctrine about which agreed-to prices are morally acceptable and which are morally unacceptable. However, despite the acuity of some of Locke’s observations, no such coherent doctrine emerges from Locke’s discussions of these examples. Indeed, many of the conclusions Locke reaches as he moves from example to example are implausible in themselves or inconsistent with one another. Nevertheless, not all is lost. Locke’s observations can be viewed as thought experiments on his part which, in conjunction with insights from Locke’s other economic writings, indicate what features a doctrine of acceptable and unacceptable prices needs to possess. I show how a line of argument which appears almost as a sidebar within “Venditio” offers a doctrine that provides those needed features. That doctrine affirms both “the common law of traffic” and “the common law of charity” and a view about when the latter takes priority over the former.